The Evaluation of Prospective Teachers' Perceptions of the Competencies That Teachers Should Possess in the 21st Century - Tekman, Tülay Kaya (Cadernos de Educação Tecnologia e Sociedade, 2024)
The history of the teaching profession dates back as far as the beginning of humanity. As a social and communal being, humans have always been in effort transfer their knowledge to future generations throughout the ages. It is obvious that the teaching profession will exist in every age and in every society as long as humanity exists. However, as significant developments, the requirements of the age, the desired profiles of individuals, and changes in the profession lead to differences in education programs, the competencies that teachers should possess are also shaped according to the era in which they live. The related literature was reviewed and it was revealed that no such study had been conducted in the TRNC. This study aims to reveal the prospective teachers’ perspectives on the competencies that the teachers should have in the 21st century. This study was conducted with 31 teacher candidates studying in the 4th grade at Near East University and Girne University in TRNC in the fall semester of the 2023-2024 academic year. The research was conducted with qualitative research method and case study design was used in the research. Data were collected by using a semi-structured interview form which was prepared by the researcher and it consisted of three questions. The data were analysed with descriptive analysis and direct quotations from the views of the teacher candidates were included. The results showed that he teacher candidates are aware of 21st century skills.